A qualitative descriptive study of new graduate nurses' experiences supporting breastfeeding women in neonatal settings. (August 2021) - Prokop, Nicole; Sim, Jenny; Meedya, Shahla
Abstract: Aim: The aim was to explore the experiences of new graduate nurses who provide support to breastfeeding women in neonatal care settings. The objective of this study was to explore the enablers and barriers that influenced new graduate nurses' self-efficacy. Background: Nurses have important roles in promoting and educating breastfeeding women in neonatal care settings. Although there are many studies that focused on nursing students and registered nurses' experiences in supporting breastfeeding women, there is limited research about the experiences of new graduate nurses during their transition from universities to neonatal care settings as a registered nurse where they learn how to educate and support breastfeeding women. Design: A qualitative descriptive study. Methods: Nine new graduate nurses who support breastfeeding women in neonatal care settings within Australia were recruited. Data was collected through semi-structured interviews via videoconference or telephone. Braun & Clarke's thematic analysis was used to analyse the data. Results: This study found four themes: Preparedness, Emotions, Ongoing Learning, and Confidence. Barriers and enablers included support, time, consistency of information, and impact of stereotyping. The new graduate nurses did not initially feel prepared to support breastfeeding women due to their lack of knowledge. Participants' self-efficacy enhancing strategies to help build knowledge and confidence supporting breastfeeding women included: a) frequent practice, b) having role models and seeking support, c) receiving encouragement and positive feedback, and d) interpreting their emotional feelings as a normal reaction to the learning process. Conclusion: Additional education should be provided during pre-registration education and on commencement of employment in neonatal settings to improve new graduate nurses'knowledge supporting breastfeeding women. Self-efficacy enhancing strategies can be used in partnerships between educational institutions and hospitals to support new graduate nurses to feel more confident providing breastfeeding support in neonatal care settings. Highlights: New graduate nurses who work in neonatal care settings report feeling unprepared. New graduate nurses lack the necessary confidence to support breastfeeding women. Self-efficacy enhancing strategies helped improve both preparedness and confidence. Both pre-registration institutions and hospitals must provide additional education. This breastfeeding education should apply self-efficacy enhancing strategies.